2005
DOI: 10.1128/aem.71.3.1254-1258.2005
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 1,4-Dioxane and Cyclic Ethers by an Isolated Fungus

Abstract: By using 1,4-dioxane as the sole source of carbon, a 1,4-dioxane-degrading microorganism was isolated from soil. The fungus, termed strain A, was able to utilize 1,4-dioxane and many kinds of cyclic ethers as the sole source of carbon and was identified as Cordyceps sinensis from its 18S rRNA gene sequence. Ethylene glycol was identified as a degradation product of 1,4-dioxane by the use of deuterated 1,4-dioxane-d 8 and gas chromatography-mass spectrometry analysis. A degradation pathway involving ethylene gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
123
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(128 citation statements)
references
References 29 publications
2
123
0
1
Order By: Relevance
“…Among these organisms are multiple Rhodococcus isolates, including Rhodococcus ruber strains 219 (2,3) and M2 (12), a number of closely related Pseudonocardia strains, including Pseudonocardia dioxanivorans (25,35), Pseudonocardia benzenivorans (17), Pseudonocardia sulfidooxydans (17,27), Pseudonocardia hydrocarbonoxydans (17), and Pseudonocardia tetrahydrofuranoxydans strains K1 (21), M1 (12), and ENV478 (45), and the Nocardia-like propanotroph strain ENV 425 (45). Fungal growth on THF by Aureobasidium pullulans has been reported for a patent (36), and growth of Cordyceps sinensis on THF, tetrahydropyran, and other cyclic ethers, including 1,3-dioxane (13D), 1,4-dioxane (14D), and several methyl dioxanes, was also recently described (33). The Cordyceps strain generates ethylene glycol during 14D catabolism, and a similar pathway appears to operate in a recently described 14D-metabolizing bacterium, Mycobacterium sp.…”
mentioning
confidence: 99%
“…Among these organisms are multiple Rhodococcus isolates, including Rhodococcus ruber strains 219 (2,3) and M2 (12), a number of closely related Pseudonocardia strains, including Pseudonocardia dioxanivorans (25,35), Pseudonocardia benzenivorans (17), Pseudonocardia sulfidooxydans (17,27), Pseudonocardia hydrocarbonoxydans (17), and Pseudonocardia tetrahydrofuranoxydans strains K1 (21), M1 (12), and ENV478 (45), and the Nocardia-like propanotroph strain ENV 425 (45). Fungal growth on THF by Aureobasidium pullulans has been reported for a patent (36), and growth of Cordyceps sinensis on THF, tetrahydropyran, and other cyclic ethers, including 1,3-dioxane (13D), 1,4-dioxane (14D), and several methyl dioxanes, was also recently described (33). The Cordyceps strain generates ethylene glycol during 14D catabolism, and a similar pathway appears to operate in a recently described 14D-metabolizing bacterium, Mycobacterium sp.…”
mentioning
confidence: 99%
“…A number of pure and mixed cultures of bacteria and fungi have been reported to degrade dioxane aerobically (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), while only one study has reported anaerobic degradation (13). To date, nine microorganisms have been reported to be capable of growth on dioxane as a sole carbon and energy source (i.e., metabolism of dioxane), including Rhodococcus ruber 219 (1), Mycobacterium sp.…”
mentioning
confidence: 99%
“…To date, nine microorganisms have been reported to be capable of growth on dioxane as a sole carbon and energy source (i.e., metabolism of dioxane), including Rhodococcus ruber 219 (1), Mycobacterium sp. strain PH-06 (12), Pseudonocardia dioxanivorans CB1190 (3,14), Pseudonocardia benzenivorans B5 (11), the fungus Cordyceps sinensis (9), and four recently isolated strains identified as two Mycobacterium spp., a Pseudonocardia sp., and a Gram-negative Afipia sp. (15).…”
mentioning
confidence: 99%
“…Metabolic degradation is less common, with only a few microorganisms being able to use dioxane as the sole source for carbon and energy (18,(30)(31)(32). Cometabolic pathways include several monooxygenase enzymes required for dioxane degradation, including the methane (MMO), propane (PrMO), phenol (PHE), tetrahydrofuran (THFMO), and toluene (TOL, T4MO, or RMO), monooxygenases (19,20,28,33,34).…”
mentioning
confidence: 99%